A enfermeira e a saúde do escolar - Rodrigues, Maria da Graça Soler; Freitas, Kênia Silva dos Santos; Silveira, Maria de Fátima Novo; Assumpção, Janine Pereira (VITTALLE - Revista de Ciências da Saúde, 2017)
Ver no documento